Synthesis and Characterization of 1,10-Phenanthroline-2,9- dicarbaldehyde-bis-(thiosemicarbazone) - Shabaan, Samira; Letafat, Bahram; Esmati, Nasim; Shafiee, Abbas; Foroumadi, Alireza (Asian Journal of Chemistry, 2012)
In this work, 1,10-phenanthroline-2,9-dicarbaldehyde-bis-(thiosemicarbazone) having N and S donor atoms has been synthesized and characterized by 1H NMR, IR and mass spectroscopy. Having bis-(thiosemicarbazone) on phenanthroline ring, it should be considered as a useful ligand in coordination chemistry.